PBL-Based Learning Media for Division and Multiplication (PEKA) in Mathematics Content on Division and Multiplication Material in Grade IV Elementary School - I Gusti Agung Warastri Praharsini; I Wayan Wiarta; Putu Aditya Antara (Universitas Pendidikan Ganesha, 2025)
The low learning outcomes of students in multiplication and division are attributed to the limited use of interactive learning media and the lack of learning motivation. This condition highlights the need for developing innovative media based on Problem Based Learning (PBL) to enhance learning effectiveness and student engagement. This study aims to develop, analyze the feasibility, and examine the effectiveness of the PEKA interactive learning media based on PBL for teaching multiplication and division in elementary education. The research employs a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The participants included subject matter experts, instructional design experts, media specialists, and fourth-grade students. The instruments consisted of validation questionnaires and learning achievement tests, while data were analyzed using quantitative descriptive, qualitative descriptive, and inferential statistical methods. The feasibility results indicated that all evaluated aspects achieved scores ranging from 88.89% to 94%, categorized as good to very good. The t-test results showed that tcount > ttable (1.989 > 1.701), indicating a significant improvement in students’ learning outcomes. It can be concluded that the PBL-based PEKA media is feasible and effective in enhancing students’ understanding and learning achievement. The implication suggests that this media can serve as an innovative alternative to foster interactive, contextual, and student-centered mathematics learning while strengthening critical thinking skills.